The Evolution of Malay Morphophonemics from the 16th to the 20th Century: (Evolusi Morfofonemik Bahasa Melayu dari Abad Ke-16 Hingga Abad Ke-20) (Jurnal Bahasa, 2018)
This study aims to investigate and analyse the process of morphophonemics as a result of adding affixes meN- and meN… kan to words found in seventeen selected texts from the 16th century to the 20th century. It also aims to determine the extent to which Asmah's argument that the Malay language in the 16th and 17th century had undergone morphophonemic changes can be verified. The analysis applies the theory of generative phonology and ordered phonological rules. Findings reveal that the Malay language had experienced the process of morphophonemic change in the 16th and 17th century. As well, the findings show that there was a gradual decrease of words that retain or omit the initial phoneme when merging with the prefix meN- over the past centuries. Since this phenomenon is absent in present standard Malay, it helps to further strengthen Asmah's argument.Keywords: morphophonemic process, changes of Malay language, generative phonology theory, ordered phonological rules